2012
DOI: 10.1007/s11306-012-0456-y
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale neurochemical metabolomics analysis identifies multiple compounds associated with methamphetamine exposure

Abstract: Methamphetamine (MA) is an illegal stimulant drug of abuse with serious negative health consequences. The neurochemical effects of MA have been partially characterized, with a traditional focus on classical neurotransmitter systems. However, these directions have not yet led to novel drug treatments for MA abuse or toxicity. As an alternative approach, we describe here the first application of metabolomics to investigate the neurochemical consequences of MA exposure in the rodent brain. We examined single expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 63 publications
3
44
0
Order By: Relevance
“…Extracts reconstituted in acidic conditions were gradient eluted using water and methanol, both containing 0.1% formic acid, while the basic extracts, which also use water/methanol, contained 6.5 mM ammonium bicarbonate. The MS analysis was alternated between MS and data-dependent MS 2 scans using dynamic exclusion (McClay et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracts reconstituted in acidic conditions were gradient eluted using water and methanol, both containing 0.1% formic acid, while the basic extracts, which also use water/methanol, contained 6.5 mM ammonium bicarbonate. The MS analysis was alternated between MS and data-dependent MS 2 scans using dynamic exclusion (McClay et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Ions with counts under two million required more effort to characterize. Fragmentation spectra (MS/MS) were typically generated in data dependent manner, but where necessary, targeted MS/MS was employed, such as in the case of lower level signals (McClay et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolomics provides a useful tool to analyze metabolite concentrations in physiological and biological states. It is therefore applied to explore biomarkers for disease diagnosis [1][2][3][4] and to assess drug responses and toxicity [5][6][7][8]. Various metabolomic approaches are used, and among these, lipidomics includes the comprehensive analysis of lipid metabolites [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Besides energy metabolism and oxidative stress, alterations in other mitochondrion-related mechanisms and functions have been reported [21,40,41,42]. The majority of these studies have used proteomics approaches, as mitochondrion-specific metabolomics in psychiatry is just beginning to be applied [43]. These studies have revealed alterations in mitochondrial import, transport and structural elements in high versus low trait anxiety mice [21,40], in mitochondrion-orchestrated apoptosis in a mouse model of schizophrenia-like symptoms [41] and in structural mitochondrial components in a methamphetamine-induced behavioral sensitization mouse model of schizophrenia-related symptoms [42].…”
Section: Proteomics and Metabolomics Studies In Psychiatric Disordersmentioning
confidence: 99%